Orbital solutions for six spectroscopic binaries with circular or nearly circular orbits - Komonjinda S. (2017)
Six southern spectroscopic binary systems were selected in this programme. The systems selected were shown to have circular or nearly circular orbits (e < 0.1) from earlier published solutions of only moderate precision. The purpose was to obtain high-precision radial velocity data in order to investigate the reality of the small eccentricities and possibly to study the circularization of binary star orbits for systems of different age. The High Efficiency and Resolution Canterbury University Large Échelle Spectrograph (HERCULES) and 1-m McLellan telescope at Mt John Observatory, New Zealand, were used to obtain nearly 500 CCD spectra between 2004 October and 2006 July. Radial velocities were obtained by cross-correlation. These data were used to achieve high-precision orbital solutions for all the systems studied, often with solutions up to 70 times more precise than those from the earlier literature. However, the precision of the solutions is limited in some cases by the rotational velocity or chromospheric activity of the stars. A discussion of further binaries observed in this programme and of the significance of small eccentricities obtained for close binaries is undertaken in subsequent papers. © 2010 The Authors. Journal compilation © 2010 RAS.